Active8! Technology-based intervention to promote physical activity in hospital employees - Blake, Holly; Suggs, L. Suzanne; Coman, Emil; Aguirre, Lucia; Batt, Mark E. (SAGE Publications, 2017)
Purpose: Increase physical activity in healthcare employees using health messaging, and compare email with mobile phone short-message service (SMS) as delivery channels. Design: Randomised controlled trial Setting: UK hospital workplace Subjects: 296 employees (19-67 years, 53% of study website visitors) Intervention: 12-week messaging intervention designed to increase physical activity and delivered via SMS (n=147) or email (n=149); content tailored using Theory of Planned Behaviour (TPB) and limited to 160 characters. Measures: Baseline, 6, 12 and 16 weeks. Online measures included TPB constructs; physical activity behaviour on the Global Physical Activity Questionnaire; health-related quality of life on the Short-Form 12. Analysis: General linear models for repeated measures. Results: Increase in duration (mean hours/day) of moderate work-related activity and moderate recreational activity from baseline to 16 weeks. Short-lived increase in frequency (days/week) of vigorous recreational activity from baseline to 6 weeks. Increase in duration and frequency of active travel from baseline to 16 weeks. Emails generated greater changes than SMS in active travel and moderate activity (work and recreational). Conclusion: Minimal physical activity promotion delivered by SMS or email can increase frequency and duration of active travel, and duration of moderate-intensity physical activity at work and for leisure, which is maintained up to one-month after messaging ends. Both channels were useful platforms for health communication; emails were particularly beneficial with hospital employees.